(untitled) (World Bulletin of Public Health, 2025)
The integration of dermatology and preventive medicine is crucial in reducing the burden of skin diseases. Skin disorders, ranging from common conditions such as acne and eczema to more severe diseases like melanoma, pose significant challenges to public health. Preventive medicine plays a critical role in early detection, risk assessment, and health promotion. This paper explores modern strategies for preventing skin diseases, focusing on lifestyle modifications, early intervention, and the use of technology in monitoring skin health. By examining evidence-based preventive measures, the article demonstrates how dermatology and preventive medicine together can improve public health outcomes, reduce healthcare costs, and enhance quality of life.